Penerapan Model Pembelajaran Kooperatif Tipe Team Game Tournament (TGT) Berbantuan Media Wordwall Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa Pada Pembelajaran IPAS Kelas VB SD Negeri 5 Kota Bengkulu - Puspita, Rahma Ayu; Dalifa, Dalifa; Yusnia, Yusnia (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aims to improve student activity and learning outcomes by using the Team Game Tournament (TGT) type cooperative learning model assisted by Wordwall media in science and science learning for class fifth B at SD Negeri 5 Bengkulu City. The type of research used is Classroom Action Research (PTK) which is carried out in two cycles. The subjects in this research were 30 students in class fifth B at SDN 5, Bengkulu City. The research instruments used were student activity observation sheets and test sheets. The data analysis technique uses the formula for average score, highest score, lowest score, score difference and range of values ​​for each criterion. Test data is processed using the formula for average score and percentage of success in learning completion. The research results showed that in cycle first it was still not optimal so it was improved in cycle second. The results of student activities in cycle first obtained a score of 23 in the sufficient category, and increased in cycle second to a score of 35.5 in the good category. In the Knowledge aspect in cycle first obtained an average score of 66.66 with a percentage of 63%. In cycle second it increased by obtaining an average score of 78.5 with a percentage of 83%. So it can be concluded that the application of the team game tournament (TGT) type cooperative learning model assisted by Wordwall media in science and science learning for class fifth B at SD Negeri 5 Bengkulu City can increase student activity and learning outcomes.